A review of the functionalities of smart walkers - Martins, Maria (2015)
There is a need to conceptualize and improve the investigation and developments in assistive devices, focusing on the design and effectiveness of walkers in the user's rehabilitation process and functional compensation. This review surveys the importance of smart walkers in maintaining mobility and discusses their potential in rehabilitation and their demands as assistive devices. It also presents related research in addressing and quantifying the smart walker's efficiency and influence on gait. Besides, it discusses smart walkers focusing on studies related to the concept of autonomous and shared-control and manual guidance, the use of smart walkers as personal helpers to sit-to-stand and diagnostic tools for patients' rehabilitation through the evaluation of their gait.